Penanaman P5P2RA melalui Kegiatan Islamic Supercamp For Kids di SDNU Galur Kulon Progo Yogyakarta - Karima, Nazhif Kayyisa; Mujawazah (IIQ An Nur Yogyakarta, 2024)
Islamic Supercamp for Kids is an initiative designed to align with President's Decree No. 20 of 2018 which has led to the implementation of the Merdeka Curriculum in Indonesian schools and the organization of activities that support the President's mandate. Islamic Supercamp for Kids is one such activity, specifically designed to strengthen these values of strong character, noble morals, and excellence in innovation and technology. This research aims to analyze how Islamic Supercamp for Kids can effectively strengthen the Pancasila Learner Profile and Rahmatan lil Alamin Learner Profile (P5P2RA), and to identify the P5P2RA values embedded within the Islamic Supercamp for Kids activities. Employing a qualitative research methodology with a case study approach, the researcher gathered data through three methods: observation, interviews, and document analysis. The research findings reveal five values of the Pancasila Learner Profile and six dimensions of the Rahmatan lil Alamin Learner Profile. Based on these findings, Islamic Supercamp for Kids can be utilized as an effective activity to reinforce the Pancasila Learner Profile and Rahmatan lil Alamin Learner Profile.